2010
DOI: 10.4314/njm.v19i4.61965
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Environmental Lead Exposure in Port Harcourt, Nigeria: Analysis of its association with renal function indices

Abstract: Background: In spite of the high risk of lead exposure in Nigeria, there is a paucity of data on the occupational and environmental burden of lead exposure and its impact on human health especially its nephrotoxic effects. This study aims to assess the degree of occupational and environmental lead exposure in Port Harcourt Nigeria and the relationship between lead exposure and indices of renal function. Methods: A cross sectional comparative study of 190 adult subjects with occupational lead exposure and 80 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
15
2
Order By: Relevance
“…Among the studied elements, lead attracted most of researchers’ attention in the past and present, and plenty of studies have documented kidney toxicity [22], cardiovascular effects, including arterial hypertension [23], genotoxicity [24], central nervous system effects [25] and reproductive toxicity [26], such as deterioration in human semen quality even in moderate exposures. The latter study showed similar effect not only for lead, but for Cd as well.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studied elements, lead attracted most of researchers’ attention in the past and present, and plenty of studies have documented kidney toxicity [22], cardiovascular effects, including arterial hypertension [23], genotoxicity [24], central nervous system effects [25] and reproductive toxicity [26], such as deterioration in human semen quality even in moderate exposures. The latter study showed similar effect not only for lead, but for Cd as well.…”
Section: Discussionmentioning
confidence: 99%
“…The occupationally exposed subjects, consisting of automobile mechanics, generator mechanics, petrol dispensing attendants in filling stations, artisanal gold-miners, battery chargers and spray painters, volunteered to participate in this study. These occupations are among those likely to expose individuals to lead toxicity [2][5]. Workers on part-time duties and those who spent less than six months on the job were excluded from this study.…”
Section: Study Design and Samplementioning
confidence: 99%
“…Lead is a ubiquitous environmental pollutant that has been detected in almost all phases of biological systems [1] [2]. Even trace amounts of lead are harmful to humans and other organisms as they induce a broad range of physiological, biochemical and behavioral dysfunctions in many parts of the body, including the central and peripheral nervous systems, hematopoietic system, cardiovascular system, kidneys, liver and reproductive systems [2][3] [27]. As a result, a safe level of lead exposure has not yet been defined [3].…”
Section: Introductionmentioning
confidence: 99%
“…Egypt has one of the highest incidences of intrauterine growth retardation, and this appears to be positively correlated with heavy metal toxicity (El-Baz et al, 2015). Lead toxicity (sometimes in combination with high cadmium exposures) has been shown to be associated with renal function impairment (Alasia et al, 2010b). Occupationally lead-exposed subjects have been shown to have significantly higher blood lead levels, as well as serum urea, creatinine, and serum uric acid levels, and other renal biomarkers and markers of nephrotoxicity.…”
Section: Health Outcomesmentioning
confidence: 99%